Sosialisasi Manfaat Pelabelan untuk Meningkatkan Nilai Tambah Produk Pangan Lokal kepada Kelompok Wanita Nelayan di Desa Bintaro, Nusa Tenggara Barat - Nur Afni; Lingga Gita Dwikasari; Setyaning Pawestri; Riezka Zuhriatika Rasyda; Siska Cicilia; Sulaemah Sulaemah (SAFARI :Jurnal Pengabdian Masyarakat Indonesia, 2026)
Food labeling that complies with regulatory requirements plays an important role in increasing consumer trust, expanding market access, and enhancing the selling value of MSME products. This community service activity aims to disseminate information on the regulations governing processed and fresh food labeling, as well as to facilitate understanding of packaging particularly labeling among MSME actors, specifically women fisher groups in Bintaro Subdistrict, Ampenan District, Mataram City, West Nusa Tenggara. This area is characterized by high urban population density and dynamic MSME-based economic activities, making the implementation of proper labeling practices highly necessary. The program consisted of three stages: preparation, implementation, and evaluation, conducted on June 2, 2025, from 08:30 to 12:00 WITA in Bintaro Subdistrict. The results of this activity showed an improvement in MSME actors’ understanding of the mandatory elements in food labels when designing fish-based processed product labels in accordance with BPOM regulations, ensuring compliance with food safety, quality, and legality standards based on applicable Indonesian laws.